The Effect Of 1,25-dihydroxyvitamin D To The Phagositosis Activity Of Children Macrophage In Tuberculosis Infection - Rosi Esa Gustina (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Children infected with TB do not always experience TB pain, depending on the number of bacteria that enter and the amount of endurance the child has. 1,25-dihydroxyvitamin D (1,25 (OH) 2D) is a function modulator for macrophages. Objective: This study aims to determine the effect of giving 1,25 (OH) 2D on the phagocytic activity of macrophages in children infected with TB. Methods: This study was an experimental Post Test Only Control Group Design study of 27 samples of children infected with TB. The 1,25 (OH) 2D concentration used was 10-8M and the concentration of 10-7M. Examination of phagocytic activity is carried out using latex beads. Results: One Way ANOVA analysis showed a significant difference in the percentage of macrophages that phagocyte latex and the average number of latex phagocytes by each macrophage between the control group and the treatment group (p